2020
DOI: 10.1002/smi.2937
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic psychological and biological responses to mindfulness‐based art therapy

Abstract: Stress and anxiety pose a threat to college students' academic performance as well as their long-term mental and physical health, but the time constraints of a rigorous academic schedule make it difficult to offer even brief mental health interventions. A convenience sample of full-time students at a public university was recruited for a 5-week study conducted mostly using an online platform. Participants were randomly assigned to a Mindfulness-Based Art Therapy (MBAT) intervention or a Neutral Clay Task (NCT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…The sample sizes across the 13 studies ranged from 23 [ 40 ] to 2110 [ 44 ]. Regarding study design, there were 46% (6/13) of RCTs with an active control [ 39 , 40 , 43 , 45 , 46 , 48 ], 38% (5/13) of RCTs with a wait-list control [ 38 , 41 , 42 , 49 , 52 ], 8% (1/13) were dismantling trials [ 41 ], and 8% (1/13) were pre-post trials [ 47 ]. The duration of the digital interventions varied, with one study reporting a single session [ 43 ], another study reporting 6 days of intervention [ 44 ], and the remaining studies (11/13, 85%) ranging from 3 to 10 weeks (mean duration =5.5, SD 2.2 weeks; mode duration=4 weeks), as presented in Table 1 [ 35 - 42 , 45 - 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample sizes across the 13 studies ranged from 23 [ 40 ] to 2110 [ 44 ]. Regarding study design, there were 46% (6/13) of RCTs with an active control [ 39 , 40 , 43 , 45 , 46 , 48 ], 38% (5/13) of RCTs with a wait-list control [ 38 , 41 , 42 , 49 , 52 ], 8% (1/13) were dismantling trials [ 41 ], and 8% (1/13) were pre-post trials [ 47 ]. The duration of the digital interventions varied, with one study reporting a single session [ 43 ], another study reporting 6 days of intervention [ 44 ], and the remaining studies (11/13, 85%) ranging from 3 to 10 weeks (mean duration =5.5, SD 2.2 weeks; mode duration=4 weeks), as presented in Table 1 [ 35 - 42 , 45 - 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The sample sizes across the 13 studies ranged from 23 [40] to 2110 [44]. Regarding study design, there were 46% (6/13) of RCTs with an active control [39,40,43,45,46,48], 38% (5/13) of RCTs with a wait-list control [38,41,42,49,52], 8%…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Many clinical studies show the effectiveness of various types of art therapy in mitigating symptoms of anxiety in different age and patient groups. Mindfulness art therapy has shown particular benefits in reducing anxiety, perceived stress and salivary cortisol in college students (Beerse et al 2020). In another study, mindfulness-based art therapy is found to significantly improve the psychological well-being, reduce the trait anxiety (measured using trait anxiety inventory), and reduce depression (measured using the Beck Depression Inventory) of Korean patients with coronary artery disease, female and male with mean age 64.81 þ/À 9.19 years (Jang et al 2018).…”
Section: D)mentioning
confidence: 99%
“…Our understanding of the physiological mechanisms by which art therapy exerts its effects is advancing (Belkofer et al, 2014;Czamanski-Cohen & Weihs, 2016;Hass-Cohen & Findlay, 2015;Kaimal et al, 2016Kaimal et al, , 2017King et al, 2017;Lusebrink, 2010;Walker et al, 2018) and the field is beginning to more accurately identify the underlying physiological mechanisms associated with emotion, cognition, and learning that enhance the capacities to change through therapy . For example, Beerse, Van Lith, and Stanwood (2020) found that anxiety and perceived stress were reduced, and salivary cortisol outcomes were used to measure the differences between a mindfulness-based art therapy (MBAT) intervention compared to an art-making task in college-aged students. This work has built upon other studies that have used physiological measures to show fluctuations in brain activity when engaging in different types of art-making tasks.…”
mentioning
confidence: 99%